2019
DOI: 10.1186/s13075-019-2040-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine inhibits IL-1β production from amyloid-stimulated human neutrophils

Abstract: BackgroundHydroxychloroquine (HCQ) is used for the treatment of patients with rheumatic diseases. We tested the hypothesis that HCQ affects the NLRP3 inflammasome, which is involved in autoinflammation.MethodsHuman neutrophils were stimulated with serum amyloid A (SAA) in vitro and measured for IL-1β and caspase-1 (p20) secretion by ELISA. Pro-IL-1β mRNA expression in human neutrophils was quantified by real-time RT-PCR.ResultsSAA stimulation induced significant production of IL-1β in human neutrophils. SAA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…These in vitro data suggest that 24 hour in vitro treatment with HCQ minimally impacts immune gene transcription and support findings that HCQ has potential immunomodulatory and lipid metabolism effects [11]. Specifically, previous work from in vivo studies has reported that HCQ treatment significantly decreased serum TNF-A and increased IL-10 levels in women following treatment with 400mg/per day orally [12] and inhibited IL-1β production from stimulated human neutrophils [13]. In the context of COVID-19 infection, clinical reports indicate severe patients exhibit a well-known immune cytokine storm that leads to multi-organ failure [14,15].…”
Section: Treatment Of Resting Peripheral Blood Mononuclear Cells Withsupporting
confidence: 79%
“…These in vitro data suggest that 24 hour in vitro treatment with HCQ minimally impacts immune gene transcription and support findings that HCQ has potential immunomodulatory and lipid metabolism effects [11]. Specifically, previous work from in vivo studies has reported that HCQ treatment significantly decreased serum TNF-A and increased IL-10 levels in women following treatment with 400mg/per day orally [12] and inhibited IL-1β production from stimulated human neutrophils [13]. In the context of COVID-19 infection, clinical reports indicate severe patients exhibit a well-known immune cytokine storm that leads to multi-organ failure [14,15].…”
Section: Treatment Of Resting Peripheral Blood Mononuclear Cells Withsupporting
confidence: 79%
“…Hydroxychloroquine and azithromycin were reported as effective anti-SARS-CoV-2 agents ( Ohe et al, 2020 ; Zhou D. et al, 2020 ). Fujita et al demonstrated that hydroxychloroquine significantly inhibited IL-1β production in activated human neutrophils in vitro ( Fujita et al, 2019 ). Hydroxychloroquine inhibited NET formation and ameliorated the hypercoagulation state in mice with orthotopic pancreatic adenocarcinoma.…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…Treatment with hydroxychloroquine was associated with impaired IL-1β production in SAA-stimulated human neutrophils without affecting the initial activation process of NLRP3 inflammasome, such as pro-IL-1β induction or NLRP3 induction. These findings suggest that hydroxychloroquine affects the activation process of NLRP3, and reduces the production of IL-1β in human neutrophils as the innate immune cells (Fujita et al 2019).…”
Section: The Effect Of Cq and Hcq On Nlrp3 Inflammasome Activationmentioning
confidence: 74%